2014
DOI: 10.3390/rs6043059
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Correlation Environment (ICE) — A Statistical Web Tool for Data Collinearity Analysis

Abstract: Web tools for statistical investigation with an interactive and friendly interface enable users without programming knowledge to conduct their analyses. We develop an Interactive Correlation Environment (ICE) in an open access platform to perform spectral collinearity analysis for biogeochemical activity retrieval. We evaluate its performance on different browsers and applied it to retrieve chlorophyll-a (chl-a) concentration in a tropical reservoir. The use of ICE to retrieve water chl-a concentration got a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Therefore, for each period, we analyzed the correlation among the spectral bands and chl-a concentration. We also evaluated the use of band ratios through the web tool, Interactive Correlation Environment (ICE), available at www.dsr.inpe.br/hidrosfera/ice [37]. This web tool builds a two-dimensional correlation plot of the radiometric measurement (i.e., surface reflectance from the MOD09GA) and its relation to the interesting biogeochemical component (i.e., chl-a).…”
Section: Band Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for each period, we analyzed the correlation among the spectral bands and chl-a concentration. We also evaluated the use of band ratios through the web tool, Interactive Correlation Environment (ICE), available at www.dsr.inpe.br/hidrosfera/ice [37]. This web tool builds a two-dimensional correlation plot of the radiometric measurement (i.e., surface reflectance from the MOD09GA) and its relation to the interesting biogeochemical component (i.e., chl-a).…”
Section: Band Selectionmentioning
confidence: 99%
“…The importance of using band ratios lies in the fact that the specular reflection from water under wavy conditions gets suppressed by the ratio architecture of this type of algorithm, which cancels out the specular reflection from the two bands used in the ratio [47]. To analyze all possible band ratios, we used the ICE [37] to generate two-dimensional correlation plots of the R 2 between chl-a concentration and band ratio values. ICE was previous described in Section 2.4.1, and more information can be found in [37].…”
Section: Band Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new regional models were created using correlation tools (correlogram plot and ICE tool - Ogashawara et al, 2014). The MODIS models (simple models (either Band 1 or Band 2), spectral difference (Band 1 -Band 2) and band ratio (Band 1/Band 2)) tested by Cui et al (2010) showed that a single-band model (Band 1) can better retrieve TSM concentrations.…”
Section: Tsm Retrieval Models: Calibration and Validationmentioning
confidence: 99%
“…The development of these empirical algorithms was conducted by calculating the correlation among different band ratios and the concentrations of chl-a and turbidity values. To perform this analysis, we used a web tool named Interactive Correlation Environment (ICE) described by [48] and available at [49]. This web tool builds a two-dimensional correlation plot of the HICO's R rs and its relation to the interested limnological parameter (i.e., chl-a or turbidity).…”
Section: Bio-optical Algorithm Developmentmentioning
confidence: 99%